2005
DOI: 10.1111/j.1365-2109.2005.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stress and storage temperature on the colour and texture of pre-rigor filleted farmed cod (Gadus morhua L.)

Abstract: This experiment deals with the e¡ects of pre-slaughter stress and storage temperature on muscle pH, ¢llet contraction, colour and texture in pre-rigor ¢lleted farmed cod ¢llets. The ¢sh were either sedated with a low dose of MS-222 (14.3 mg L À 1 ) (unstressed groups) or exposed to the air for 3 min (stressed groups) before being submerged in a benzocaine bath (150 g L À1 ). The ¢sh were then killed by a blow to the head, their gills cut, ¢lleted and ¢nally stored at either 4 or 20 1C. The stressed groups had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
90
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 27 publications
17
90
3
2
Order By: Relevance
“…The mean gaping score after 7 days of storage was 0.7 with no difference between the groups (Table 2). No significant differences were observed between our groups with regard to fillet hardness (Table 3), which is similar to the findings of Stien et al [4]. However, there were significant differences between fillet locations, where the anterior part was harder than the middle or the posterior part for all the groups.…”
Section: Biochemical and Physical Qualitysupporting
confidence: 80%
See 3 more Smart Citations
“…The mean gaping score after 7 days of storage was 0.7 with no difference between the groups (Table 2). No significant differences were observed between our groups with regard to fillet hardness (Table 3), which is similar to the findings of Stien et al [4]. However, there were significant differences between fillet locations, where the anterior part was harder than the middle or the posterior part for all the groups.…”
Section: Biochemical and Physical Qualitysupporting
confidence: 80%
“…Kristoffersen et al [5] reported a higher pH value, 7.9, for farmed cod killed with as little pre-slaughter activity as possible. In our stressed fish, the values were typical, pH 7.0, and were in accordance to previously reported pH values for stressed cod [4][5][6]. Low pH at the time of killing is widely recognised as an indicator of handling stress.…”
Section: Post-slaughter Classification Of Fish According To Stress Levelsupporting
confidence: 74%
See 2 more Smart Citations
“…Higher drip losses in turbot can be explained by the fact that the turbot fillet is relatively lean compared to the salmon fillet. Pre rigor fillets from lean species such as Atlantic cod (Gadus morhua) have approximately 6-7% drip loss after 7 days of ice storage (Kristoffersen et al 2007) and will during rigor shrink by 20% (Stien et al 2005). For species with high values of body fat, such as Atlantic salmon, the fillets will shrink approximately by 10% .…”
Section: Discussionmentioning
confidence: 99%